Search for third-generation scalar leptoquarks decaying to a top quark and a τ lepton at √s=13Te - KAYA, MİTHAT (My University, 2018)
© 2018, CERN for the benefit of the CMS collaboration.A search for pair production of heavy scalar leptoquarks (LQs), each decaying into a top quark and a τ lepton, is presented. The search considers final states with an electron or a muon, one or two τ leptons that decayed to hadrons, and additional jets. The data were collected in 2016 in proton–proton collisions at s=13Te with the CMS detector at the LHC, and correspond to an integrated luminosity of 35.9fb-1. No evidence for pair production of LQs is found. Assuming a branching fraction of unity for the decay LQ → t τ, upper limits on the production cross section are set as a function of LQ mass, excluding masses below 900Ge at 95% confidence level. These results provide the most stringent limits to date on the production of scalar LQs that decay to a top quark and a τ lepton.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)